MANAGERS’ RATING OF HUMAN RELATION SKILLS NEEDED BY BUSINESS EDUCATION GRADUATES FOR SUSTAINABILITY OF SMALL AND MEDIUM ENTERPRISES IN IMO STATE (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained human relation skills needed by business education graduates forsustainability of SMEs in Imo State. One research question guided the study while two nullhypotheses were tested. The descriptive survey research design was adopted for the study. Thesstudy was carried out in Imo State. The population of this study comprised 130 SMEs registeredwith the Imo State chamber of Commerce and Industry as at 2019. The entire population of 130registered SMEs was used for the study since the size is considered manageable. Data for thestudy was collected using a validated research questionnaire. Cronbach Alpha was used todetermine the internal consistency of the instrument which yielded a reliability coefficient valueof 0.81. Arithmetic mean and standard deviation was used to answer research questions anddetermine the homogeneity or otherwise of the respondents’ ratings. The t-test and Analysis ofVariance (ANOVA) was used to test the null hypotheses. The findings of the study revealedamong others that applying positive reinforcement when relating with others, developing goodcustomer orientation for effective operation, persuading customers and stakeholder as expectedwere highly needed human relations skill. The finding also revealed that there was no significantdifference in the mean responses of SME managers on human relation skills needed by businesseducation graduates for sustainability of SMEs based on their years of experience. Based on thefindings, it was recommended among others that business education graduates should attendmore workshops, seminars, and conferences that emphasizes on the importance of humanrelations skills for sustainability of SMEs.
Keywords: Human Relations, Skills, Sustainability, Business Education